Analisis Tingkat Kesehatan Bank Dengan Menggunakan Metode Rgec Pada PT Bank Negara Indonesia TBK - Mardiana Ibrahim; Bintang Balele; Jumriani Jumriani (PPIMAN Pusat Publikasi Ilmu Manajemen, 2023)
The importance of banking in driving development and the country’s economy, coupled with the rapid competition in the banking sector, requires banks to impove and increase their performance. Bank Indonesia has issued regulation regarding banking health, one of wich is by evaluating financial reports using the RGEC method. This type research is quantitatice research, the data source comes from secondary data. The financial report data that has been obtained is then tested using the RGEC method to determine the healthy level of the bank, in this case PT Bank Negara Indonesia Tbk 2020-2022. The results of research on bank health level seen from the Risk Profile component with the Non Performing Loan ratio for 2020 – 2021 are categorized as QUITE HEALTHY, in 2022 they are categorized as HEALTHY. The Loan to Deposite Ratio is for 2020 are categorized QUITE HEALTY, in 2021-2022 they are categorized as HEALTHY. Judging from the Good Corporate Governance component, it is categorized as HEALTHY. From the Earnings component with a Return On Asset ratio for 2020 QUITE HEALTHY, 2021 HEALTHY and 2022 VERY HEALTHY, for Net Interest Margin in 2020 – 2022 is in the HEALTY category, while the Capital component with the Capital Adequacy Ratio is in the VERY HEALTHY category.